Genetic susceptibility to infectious diseases - Kaslow, Richard A.; McNicholl, Janet; Hill, Adrian V. S. (Oxford University Press, 2008)
Infectious diseases are commonly regarded as a distinct category, with different causes and patterns than chronic or genetic disease. But in fact there are many varieties of genetic susceptibility to infection, the subject of this book, which will be divided into three sections: 1) concepts and methods, 2) genes and pathophysiologic mechanisms, and 3) infectious agents and diseases. No currently published text on either genetics or infectious diseases focuses on the genetic aspects of the special relationship between host and pathogen in the way envisioned for Section 1. No other work on the selected genes regulating immunity deals as systematically with the sequence variation/function relationships most pertinent to infection as planned for Section 2. And no other book gives as meaningful a picture of how these genes operate in infectious disease as Section 3 will.